Written Sources of the Mangit Era As An Important Source For Illuminating The History Of The Bukhara Emirate - Mamadjanov Azamjon (International Journal on Integrated Education, 2023)
In this article, the local sources on the history of the Bukhara Emirate written in the XIX-XX centuries are thoroughly studied and subjected to scientific observation on the basis of general description and primary analysis. In particular, in the article, the works of local historians such as Syed Muhammad Nasir, Muhammad Ali Baljuvani, Ahmad Donish, etc., are used scientifically.